Hypolipidemic Potential of Ethyl acetate Extract of Hyphaene thebaica Fruit in Streptozotocin-induced Diabetic Rats - Mubarak Muhammad Dahiru; Nadro Margret Samuel (Majalah Obat Tradisional, 2022)
Hyperlipidemia is characterized by elevated levels of Triglycerides, Cholesterol, LDL, and decreased levels of HDL are challenges in the management of Diabetes mellitus which might lead to death. This study aimed to determine the hypolipidemic potential of ethyl acetate extract of Hyphaene thebaica fruit in streptozotocin-induced diabetic rats. The hypolipidemic potential of H. thebaica fruit in streptozotocin-induced diabetic rats was determined. Rats were divided into six groups. Treatment groups were administered the extract at doses of 400 and 200 mg/kg body weight. Oral administration of the extract at 400 mg/kg body weight for four weeks significantly (p < 0.05) decreased the levels of total cholesterol (151.7 mg/dl ±2.40), Triglyceride (84.0 mg/dl ±1.15), LDL (75.2 mg/dl ±1.20) and increased HDL (39.3 mg/dl ±1.88) level. However no significant (p < 0.05) difference was observed between the 400 and 200 mg/kg body weight dose. Conclusively, H. thebaica can be used as a medicinal plant due to its protective action against dyslipidemic complications of diabetes mellitus.